UPVC 5 Years Serving the Community - Hernández Pinto, Carlos (Revista Universidad de Guayaquil, 2009)
The Outreach Unit is based on the Higher Education Law, which commits the country’s universities to have a Commission for Outreach to the Community.Since June 6, 2004, the University of Guayaquil has had the Outreach Unit (UPVC), an organization that executes projects linked to the student population; where more than 100 teachers and 200 university students have contributed in the technical area: architecture, engineering, medicine, medical technology, providing solutions to the main social problems.